Remote brain hemorrhage after IV thrombolysis: Role of preexisting lesions. (3rd March 2020) - Drelon, Agathe; Kuchcinski, Gregory; Caparros, François; Dequatre-Ponchelle, Nelly; Moulin, Solène; Cordonnier, Charlotte; Bordet, Régis; Pruvo, Jean-Pierre; Leys, Didier
Abstract : Objective: To test the hypothesis that remote intracerebral hemorrhages (r-ICHs) after IV thrombolysis occur in preexisting brain lesions. Method: We prospectively collected baseline data from consecutive patients treated with IV thrombolysis for cerebral ischemia and reviewed their baseline MRI scans to identify preexisting lesions in those who developed r-ICH. We evaluated outcomes with the modified Rankin Scale (mRS) and defined good outcomes as scores of 0 to 2 or similar to the preexisting mRS score. Results: Of 944 patients, 24 (2.5%) had r-ICH: lobar in 14, deep in 7, and both in 3. Sixteen of them (1.7% of all patients, 66.7% of those with r-ICH) were asymptomatic. Of the 41 r-ICHs found in these patients, 17 (41%) occurred within a lesion present before thrombolysis: 6 cerebral microbleeds (CMBs), 6 old and 1 recent infarct, and 4 areas of white matter hyperintensity. Patients with r-ICH were more likely to have strictly lobar CMBs ( p = 0.049). They were 10 years older ( p = 0.007), had a 16–mm Hg higher systolic blood pressure ( p = 0.035) at baseline, and had more CMBs ( p = 0.007). r-ICHs were better predicted by clinical (age, baseline systolic blood pressure) than imaging (purely lobar CMBs and having >5 CMBs) variables. r-ICHs tended to be associated with worse outcomes. Conclusion: We identified preexisting brain lesions in nearly half of the patients with r-ICH. All were of vascular origin, supporting the hypothesis that r-ICHs occur in preexisting brain lesions. Higher-field machines could help identifying preexisting lesions in those who developed r-ICH in an apparently normal area.